Phlebotomus perniciosus Recombinant Salivary Proteins Polarize Murine Macrophages Toward the Anti-Inflammatory Phenotype - Sumova, Petra; Polanska, Nikola; Lestinova, Tereza; Spitzova, Tatiana; Kalouskova, Barbora; Vanek, Ondrej; Volf, Petr; Rohousova, Iva (Frontiers in cellular and infection microbiology, 2020)
Phlebotomus perniciosus (Diptera: Phlebotominae) is a medically and veterinary important insect vector. It transmits the unicellular parasite Leishmania infantum that multiplies intracellularly in macrophages causing life-threatening visceral diseases. Leishmania establishment in the vertebrate host is substantially influenced by immunomodulatory properties of vector saliva that are obligatorily co-injected into the feeding site. The repertoire of P. perniciosus salivary molecules has already been revealed and, subsequently, several salivary proteins have been expressed. However, their immunogenic properties have never been studied. In our study, we tested three P. perniciosus recombinant salivary proteins-an apyrase rSP01 and yellow-related proteins rSP03 and rSP03B-and showed their anti-inflammatory nature on the murine bone-marrow derived macrophages. Even in the presence of pro-inflammatory stimuli (IFN-γ and bacterial lipopolysaccharide, LPS), all three recombinant proteins inhibited nitric oxide production. Moreover, rSP03 seems to have a very strong anti-inflammatory effect since it enhanced arginase activity, increased the production of IL-10, and inhibited the production of TNF-α even in macrophages stimulated with IFN-γ and LPS. These results suggest that P. perniciosus apyrase and yellow-related proteins may serve as enhancing factors in sand fly saliva, facilitating the development of Leishmania infection along with their anti-haemostatic properties. Additionally, rSP03 and rSP03B did not elicit the delayed-type hypersensitivity response in mice pre-exposed to P. perniciosus bites (measured as visible skin reaction). The results of our study may help to understand the potential function of recombinant's native counterparts and their role in Leishmania transmission and establishment within the host.
Keywords: psi; antiflogistika; rekombinantní proteiny; Dogs; yellow-related proteins; macrophage polarization; Mice; fenotyp; Phlebotomus; slinné proteiny a peptidy; Macrophages; Salivary Proteins and Peptides; Phenotype; zvířata; Anti-Inflammatory Agents; myši; makrofágy; apyrase; sand fly saliva; Recombinant Proteins; immunogenicity; Animals